Casa Caiada: formação humana e musical em práticas percussivas colaborativas - Santos, Catherine Furtado dos (2013)
This research has as its central theme the continuous process of the human and musical education of the members of “Grupo de Música Percussiva Acadêmicos da Casa Caiada (GMPACC)” {Academics of the Whitewashed House Percussion Music Group [AWHPMG]}. The interest in this aspect arose from my own experience with percussion activities at the university, in non-goverment organisations (NGOs) and “Maracatu” groups, in the city of Fortaleza. I was able to observe that from 2006 there has been a significant increase in the appearance of percussion groups focussed upon activities in the carnival period as well as a great demand for people to participate in these groups in the city. At CFU (Ceará Federal University) an extension project was created in 2008 to the CFU\'s Music HND Course known by the initials AWHPMG, under the co-ordenation of Prof. Dr. Erwin Schrader and conducted by me since 2009. The group has as its objective to offer a human, musical and artistic education through percussion activities in a collaborative context, especially for young people of the state schools of the Messejana neighbourhood. Since 2009 and until 2012, I confirmed that some members have been part of the project since it began its activities and it is fitting to stress that the group in not focused only upon carnival activities as it is usually presented in Fortaleza\'s percussion scene. From this constancy of group\'s rhythm section I was able to ascertain what characterises the continuous process of human and musical education and how it occurs with the permanent members of the AWHPMG (CFU) through the perspective of Musical Education in the period of the years 2009 to 2012. In order to carry out this research there were in the role of technical support authors such as Ribeiro (1996) and Miranda (2009) with regard to the theme of percussive contexts in Brazil; Prass (2004) and Schrader (2011), with research on percussion and musical education; and Matos(2008) and Freire (1996), bringing together a perspective of formative and educational processes. The methodology will be by way of a qualitative approach and with the guidelines of case studies. The instruments of data collection will be a bibliographical survey, access to documentation and the application of interviews, having as analytical method the theoretical fundaments linked to the discourse of the interviewees. Thus, the objective of the research aims analyse the continuous process of the human and musical education of the “permanent members” of the AWHPMG (CFU) under a perspective of Musical Education in the period between 2009 and 2012, aiming to contribute towards a better understanding of the formative educational environment through percussion at CFU, of the formative aspects of education and creative musical practice which percussion activities in a collaborative context may provide the the field of Musical Education.